Love Theater: Intangible Conflicts - Kristensen, Jeppe (Peripeti, 2023)
Kristensen went to Bangkok to cast a prostitute who should play the leading character in Love Theater. The performance was based on her own life-experiences as prostitute, and the article is reflecting on intangible conflicts, regarding the prejudices of an audience.